(untitled) (International relations and international law Journal, 2019)
This article addresses the issue of introducing Islamic terminology into the Chinese tradition and its development. The features of Chinese writing used in the process of cultural diffusion are also described. The reasons for the religious pluralism of the population of China, a country that for centuries has been influenced by both the West and the South, the spread of other religions and their impact on the culture, custom and life of ordinary Chinese, are revealed. The article also describes how new concepts brought by Islam and other religions were transferred to hieroglyphic graphics, and their transformation through time with the basics for regulating the complexity of socio-economic, national and political relations in Chinese society. It discusses the dissemination and periods of Islam in China, analyzes the methods of translation of used words, formed in theological literature. Special attention is paid to the Xinjiang Uygur Autonomous Region, serving as the Chinese gateway to the Middle and Near East where Islam prevails. At the same time, it is necessary to take into account the fact that the project «One-Belt, One-Way» will create on the territory of the autonomous region a network of highways and communications that will further connect China with the world in general, and with the Islamic world in particular. Key words: cultural revolution, community, religious tradition, syncretism, holocaust, literature, policy.